Mono‐ and dinuclear CuII complexes of the benzyldipicolylamine (BDPA) ligand: crystal structure, synthesis and characterization. Issue 11 (7th November 2017) - Sivanesan, Dharmalingam; Youn, Min Hye; Park, Ki Tae; Kim, Hak Joo; Grace, Andrews Nirmala; Jeong, Soon Kwan
Abstract : Copper complexes ligated by benzyldipicolylamine (BDPA) are described. Intermolecular O—H…O(triflate), O—H…O(tetrahydrofuran), C—H…F(triflate) and C—H…O(triflate) hydrogen bonds stabilize the crystal lattice of both structures. Abstract : The crystal structures of mono‐ and dinuclear Cu II trifluoromethanesulfonate (triflate) complexes with benzyldipicolylamine (BDPA) are described. From equimolar amounts of Cu(triflate)2 and BDPA, a water‐bound Cu II mononuclear complex, aqua(benzyldipicolylamine‐κ 3 N, N′, N ′′)bis(trifluoromethanesulfonato‐κ O )copper(II) tetrahydrofuran monosolvate, [Cu(CF3 SO3 )2 (C19 H19 N3 )(H2 O)]·C4 H8 O, (I), and a triflate‐bridged Cu II dinuclear complex, bis(μ‐trifluoromethanesulfonato‐κ 2 O : O ′)bis[(benzyldipicolylamine‐κ 3 N, N′, N ′′)(trifluoromethanesulfonato‐κ O )copper(II)], [Cu2 (CF3 SO3 )4 (C19 H19 N3 )2 ], were synthesized. The presence of residual moisture in the reaction medium afforded water‐bound complex (I), whereas dinuclear complex (II) was synthesized from an anhydrous reaction medium. Single‐crystal X‐ray structure analysis reveals that the Cu II centres adopt slightly distorted octahedral geometries in both complexes. The metal‐bound water molecule in (I) is involved in intermolecular O—H…O hydrogen bonds with triflate ligands and tetrahydrofuran solvent molecules. In (II), weak intermolecular C—H…F(triflate) and C—H…O(triflate) hydrogen bonds stabilize the crystal lattice. Complexes (I) and (II) were also characterized fully using FT–IR and UV–Vis spectroscopy, cyclic voltammetry and elemental analysis.